Improving Students’ Reading Comprehension by Using Story Pyramid and Plus Minus Interesting Strategy - Elfriman Gea; Erika Sinambela; Kammer Tuahman Sipayung (LP2M STIT Palapa Nusantara, 2023)
This research shows that there were several problems faced by students at SMA Negeri 2 Alasa in learning English, especially learning reading comprehension. Therefore, researcher was interested in conducting research entitled